"Thursdays in Black campaign" and the blackening of the widow"s body: A hermeneutic of suspicion to blackening of the body to resist gender-based violence - Chisale, Sinenhlanhla S. (HTS teologiese studies, 2021)
Black is used as a colour of darkness, death, evil, bad luck and mourning. Generally, most cultures around the world use black as a colour of mourning, and widows from the African culture, in particular, are expected to wear all-black attire for a year to mourn their husbands. Although this colour is associated with death and mourning, contemporary women’s movements have reintroduced black as a colour of resistance and resilience. This article applies African feminist critical hermeneutics of suspicion to the Thursdays in Black (TIB) campaign and blackening of the widow’s body and attire. The aim is to explore how this campaign is contrary to the blackening of the widow’s body and attire in their cause and how the campaign’s wearing of black is emotionally divorced from the struggles of widows who experience distress, sadness and shame by wearing the black attire.Contribution: The article applies an African feminist hermeneutics of suspicion to the colour black used by the TIB campaign for solidarity with victims of sexual and gender-based violence (SGBV). It questions the relevance of this campaign to a widow who puts on a black attire for mourning.